Long COVID in Uganda: Electrographic findings among patients at risk - Andrew Weil Semulimi; Charles Batte; Daniel Iraguha; Pamela Apio Okwir; Hope Atuhaire; Chelsea Lipoto; Tonny Muwonge; Norah Namirembe; Grace Biyinzika Lubega; Provia Ainembabazi; John Mukisa; Felix Bongomin; et al. (Wiley, 2023)
Abstract Background COVID‐19 has a significant cardiovascular involvement. An electrocardiographic (ECG) abnormalities among people at a risk of Long COVID in Uganda was investigated. Methods A cross‐sectional study was conducted from February to June 2022 at the post COVID‐19 clinic in Mulago National Specialized Hospital, Kampala. A standard resting ECG was performed on individuals at least 2 months following acute COVID‐19, with a negative SARS‐CoV‐2 reverse‐transcription polymerase chain reaction. Socio‐demographic and clinical characteristics as well as vital signs were recorded for all study participants. Results Of the 244 study participants, 117 (47.9%) were female. The median age of all the participants was 33.0 (interquartile range: 26.0-43.5) years. Twenty‐five (10.2%) participants had a history of smoking, whereas 117 (48%) had a history of alcohol intake. In total, 46 (18.9%) had abnormal ECG findings (95% Confidence Interval [CI]: 14.39-24.29), and nonspecific T‐wave inversion (n = 16, 34%) was the most frequent ECG abnormality. The proportion of participants with ECG abnormalities was 48% lower among females (adjusted prevalence ratio [aPR]: 0.52, 95% CI: 0.28-0.96, p value <0.05) and twofold greater for those with a history of smoking (aPR: 2.03, 95% CI: 1.096-3.776, p value <0.05). Conclusion One in five Ugandans who were checked at the clinic at a risk of Long COVID showed ECG abnormalities. ECG screening is suggested to be integrated into the follow‐up care of those at a risk of Long COVID.